The Role of Modern Information Technologies in Promoting Scientific Research in Saudi Universities: Challenges, Requirements, and Future Opportunities - Alsabaan, Ashwaq Abdulhakeem (Arab Journal for Sciences and Research Publishing, 2025)
The research aimed to identify the role of modern information technologies in enhancing scientific research in Saudi universities, focusing on challenges, requirements, and future opportunities. It utilized an inductive approach as its research methodology and employed theoretical framework analysis as a tool. The study revealed several key findings, including challenges related to technological infrastructure, funding for scientific research, and policies within universities. Approximately 45% of students at King Faisal University rely on social networks to achieve their research objectives. King Faisal University identified several entities responsible for managing information technology, including the IT Infrastructure Library, COBIT, ISO, CMMI, and PMI, The modern technology tools relied upon in research include Google Scholar, EBSCO, Open Library, Zotero, SPSS, Visual Studio Code, WiseoneK, and ChatGPT, Saudi Arabia has prioritized the implementation of advanced technological infrastructure to support scientific research and improve the global ranking of its universities. In 2003, there were no Saudi universities in global rankings, but by 2016, three universities ranked among the top 500 worldwide. The "Horizons" plan for higher education aims to integrate e-learning technologies into university education. The research recommended developing blended learning models that combine traditional education with e-learning and creating shared digital platforms to facilitate collaboration among researchers from various universities.
Keywords: Information technologies; scientific research; Saudi universities